Application of microalgae in wastewater treatment with special reference to emerging contaminants: a step towards sustainability - Kundu, Pritha; Dutta, Nalok; Bhattacharya, Sayan (Frontiers in Analytical Science, 2024)
Emerging contaminants includes diverse types of synthetic or natural chemical compounds which are not detected, monitored, or controlled in the environment regularly and are released from anthropogenic activities. Substantial quantities of emerging contaminants can be found in the wastewater, originating from agro-industrial and industrial outlets, containing oil and grease, heavy metals, and harmful chemicals. Different species of microalgae can be applied in biological remediation of such contaminants in wastewater. This research emphasizes the multifaceted roles of microalgae in wastewater treatment in context of pollutants, especially the removal of emerging contaminants. A comprehensive overview of different emerging contaminant removal processes was conveyed through an in-depth examination and depiction of the uptake mechanisms employed by microalgae in wastewater treatment in this review. The final section of this review focuses on the articulation of difficulties and prospects for the future of microalgae-based wastewater treatment technology. It is subsequently established how the microalgal technologies for emerging contaminant remediation can be helpful to achieve Sustainable Development Goals (SDGs). This review establishes the connection between phytoremediation technologies with Sustainable Development, and shows how successful implementation of such technologies can lead to the remediation of emerging contaminants and effective management of wastewater.